Gender mainstreaming in education : a reference manual for governments and other stakeholders - Leo-Rhynie, Elsa (Commonwealth Secretariat LondonGB, 1999)
Targets development policy-makers, planners, and other stakeholders who aim to mainstream gender in the education sector. Defines gender and gender mainstreaming and differentiates between gender equity and gender equality. Looks at topics including: global and commonwealth mandates and trends in the education sector; gender in the education sector; strategies and processes for mainstreaming gender in the education sector. Provides analytical tools and guidelines for conducting a gender impact analysis. Examines the status of education of women and men in Ghana, Jamaica and CARICOM, Pakistan and Zambia.